Performance enhancement of a hybrid multi effect evaporation/membrane distillation system driven by solar energy for desalination. Issue 6 (December 2022) - Elhenawy, Y.; Moustafa, G.H.; Attia, Attia Mahmoud; Mansi, A.E.; Majozi, Thokozani; Bassyouni, M.
Abstract: The development of novel and energy-efficient desalination technologies has been inspired by the global water shortage and rising fossil oil prices. The current study aimed to incorporate solar energy into a hybrid water desalination set up including thermal desalination and membrane distillation (MEE-MD) technologies. This technology was demonstrated utilizing multi-effect evaporation (MEE) and air-gap membrane distillation (AGMD) structures. The performance of the hybrid desalination system with heat recovery (MEE-HR/MD), which is powered by an evacuated tube heat pipe solar collector, was evaluated outdoors under a variety of climatic conditions. Results showed that hybrid MEE/MD configurations surpassed the standalone multi-effect evaporation unit. The performance ratio of the hybrid system is 45% higher than the standalone MEE. The hybrid proposed system has a fresh potable water production capacity of 159, 84 m 3 per year at a cost of US $ 5.37/m 3 and minimizes carbon dioxide emissions by 189 tons per year. Highlights: Hybrid desalination system reduced carbon dioxide emission to 189 tons/year. The maximum energy consumed reduced by 56% using heat recovery system. Experimental and simulation study of hybrid MEE-MD systems driven by solar energy. Reducing the cost of produced freshwater using MEE-HR/MD system to US$ 5.37/m 3 .